Edukasi Tentang Motivasi Kerja dan Budaya Organisasi Melalui Media Poster kepada Karyawan Kantor Berita Online X di Surakarta - Neni Kumalasari; Norma Setya Anggraini; Sri Mentari; Sigit Santoso (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Organizations need human resources as the main support in achieving the desired goals. Quality human resources are able to contribute to advancing the organization and increasing organizational productivity. Employee performance is influenced by several factors including work environment, work discipline, organizational culture, leadership, and work motivation. However, there are still many employees who are not optimal in carrying out their responsibilities due to a lack of work motivation and poor organizational culture. One effort that can be made to overcome this problem is by providing education through print media such as posters. The aim of this psychoeducational activity is to increase employee work motivation and awareness, especially employees at one of the news agencies in the city of Surakarta, to create a good organizational culture. The methods used in implementing this activity are observation and psychoeducation through posters. The target of this activity is employees who work at one of the news agencies in the city of Surakarta. The results of this activity are positive changes shown by employees in terms of work discipline and enthusiasm in carrying out their work..